The relationship between the barbell trajectories of snatch and BCH angles - Chen, Y. H.; Chiu, H. T. (ISBS - Conference Proceedings Archive (Konstanz), 2011)
The purpose of this study is to investigate the relationship between the barbell trajectories of snatch and the angle between the projection vector of 7th cervical spinous process (C7) to barbell and the projection vector of C7 to hip joint in the sagittal plane (BCH angles) in different events. The ten weightlifters were divided into two groups according to their barbell trajectories (BT was categorized into the backward barbell trajectories, and the FT was forward). The results show that the BCH angles at PB and MF in BT are smaller than FT. The weightlifers with the backward trajectories usually make better performances. After analysis, we find out that the backward trajectories would reduce the BCH angles. The present study suggests that catching the bar with backward trajectories and smaller BCH angles at PB and MF are perhaps a better technique for snatch.